Masificación del voleibol en las Escuelas y Colegios de la Zona Sur de Machala durante el año 2012. - Díaz Freire, Edwin Vinicio (2012)
The discipline of volleyball in the city of Machala and El Oro province, has had an arrest in their sports development by the lack of new athletes in different divisions or categories, this has led to the search of sports talents using the massification as an alternative .